HbA1c Test as a Tool in the Diagnosis of Gestational Diabetes Mellitus - Renz, Paula Breitenbach (PLoS One, 2015)
AIMS: Gestational diabetes mellitus (GDM) is a prevalent and potentially serious condition which may put both mothers and neonates at risk. The current recommendation for diagnosis is the oral glucose tolerance test (OGTT). This study aimed to determine the usefulness of HbA1c test as a diagnostic tool for GDM as compared to the traditional criteria based on the OGTT. METHODS: This was a diagnostic test accuracy study. We performed OGTT and HbA1c test in women attending prenatal visits at a tertiary hospital. GDM was defined according to WHO1999 or ADA/WHO 2013 criteria. ROC curve was used to evaluate the diagnostic performance of HbA1c. Sensitivity, specificity and likelihood ratios for different HbA1c cut-off points were calculated. RESULTS: Of the 262 women in the third trimester of gestation enrolled in the study, 86 (33%) were diagnosed with GDM. Only five of these women presented HbA1c ≥48 mmol/mol (6.5%). This cut-off point presented 100% specificity but very low sensitivity (7%). Based on ROC curve, and considering OGTT as the reference criterion, HbA1c ≥40 mmol/mol (5.8%) showed adequate specificity in diagnosing GDM (94.9%) but low sensitivity (26.4%). Unlike, HbA1c values of 31 mmol/mol (5.0%) presented adequate sensitivity (89.7%) but low specificity (32.6%) to detect GDM. For women with HbA1c ≥40 mmol/mol (5.8%), the positive and negative likelihood ratios were 5.14 (95%CI 2.49–10.63) and 0.78 (0.68–0.88), respectively. The post-test probability of GDM was about 40%, representing a 4.0-fold increase in the mean pre-test probability. This cut-off point could eliminate the need for the unpleasant and laborious OGTT tests in almost one third of cases, as 38% of patients with GDM may be diagnosable by HbA1c test alone. CONCLUSIONS: Our results show that combined HbA1c and OGTT measurements may be useful in diagnosing GDM.